Design and Implementation of Solar Street Light for Scarcely Electrified Areas - Okandeji, A. A.; Jagun, Z.O.; Olajide, M. B.; Onaifo, F. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Streetlights are usually powered by alternating current supply from distribution stations of  the utility companies. This invariably increases the demand for power distribution from utility companies. Recent developments, however, suggest the possibility of the use of renewable energy sources to power streetlights in order to reduce the demand on the consumption rate of energy on the utility companies. Accordingly, this work considered the design and implementation of streetslights in scarcely electrified areas powered by solar energy. Using tilted solar modules, energy efficient lamps, and structural anticorrosion parts, a standalone streetlight configuration with automatic switch ON/OFF mechanism was built. The results show that streetlight powered by solar source of renewable energy cheaply generates electricity directly from sunlight without emissions, noise, or vibration. Therefore, due to the inconsistencies surrounding the generation of electricity using fossil fuels, this work offers an alternative source to power streetlights thereby reducing pressure on the national grid.